LEXICAL HEDGES IN ONLINE PRESENTATION AT INDONESIAN EFL CLASSROOM SETTINGS - Sarira, Pret; Mahmud, Murni; Burhamzah, Muftihatirrahmah (Universitas Negeri Makassar, 2023)
Since the discourse analysis covered a wide range of disciplines to describe the activities and the language in those disciplines included in education, the phenomena of language use in the class still become the object of study ever since the languages are essential aspects of classroom interaction. The communicative styles of the lecturers and students will be influenced by many aspects. One of them is the attendance of lexical hedges in their utterances. For that purpose, of this article is directed to explore the occurrence of lexical hedges in EFL classrooms with online class settings. This research applied a qualitative research design taking one class and the students in Universitas Negeri Makassar as the subject. The data of this research were collected by employing classroom observation and audio recording. The data were analyzed descriptively by adopting the Discourse Analysis approach which relies on data recording, data transcription, data selection, and data interpretation. Furthermore, this research employed the theory from (Namasaraev, 1997) in categorizing the lexical hedges and the data were obtained from the observation in online classroom settings through the application called ZOOM. The result of the research shows that the presenters employed lexical hedges in their utterances during the process of presentation and discussion which can be seen from the table in the findings section. This study also found that there are a bit differences in the way men and women pronounce the hedges and the researcher also found support data for the research from Nikula (1997). The findings from this study are worthy of reading for English language teaching practitioners in their effort to create effective classroom interaction.